Technology has effect on human endurance - Abd Razak, Dzulkifli (2008)
BY now, practically everyone would know who is referred to as the "Flying Fish". He is none other than Michael Phelps, the 23yearold wondersportsman of the Beijing Olympics. He has won eight gold medals in a single Olympics, the most in modern times. On top of that, he has broken at least seven world records. In one of the events, he scrapped by the slimmest of margins, 0.01 of a second to be exact, to beat his nearest opponent and clinch the 100metre butterfly. Such are the memories of what seems to be the world's most glamorous Olympics thus far. Another unforgettable memory perhaps is when a top sprinter another favourite at the Games, sadly missed his opportunity by a mere 0.02 of a second.